Xanthine oxidase and aldehyde oxidase contribute to allopurinol metabolism in rats - Yoshitaka Tayama; Kazumi Sugihara; Seigo Sanoh; Katsushi Miyake; Shigeyuki Kitamura; Shigeru Ohta (BMC, 2022)
Abstract Background Allopurinol is used to treat hyperuricemia and gout. It is metabolized to oxypurinol by xanthine oxidase (XO), and aldehyde oxidase (AO). Allopurinol and oxypurinol are potent XO inhibitors that reduce the plasma uric acid levels. Although oxypurinol levels show large inter-individual variations, high concentrations of oxypurinol can cause various adverse effects. Therefore, it is important to understand allopurinol metabolism by XO and AO. In this study we aimed to estimate the role of AO and XO in allopurinol metabolism by pre-administering Crl:CD and Jcl:SD rats, which have known strain differences in AO activity, with XO inhibitor febuxostat. Methods Allopurinol (30 or 100 mg/kg) was administered to Crl:CD and Jcl:SD rats with low and high AO activity, respectively, after pretreatment with or without febuxostat. The serum concentrations of allopurinol and oxypurinol were measured, and the area under the concentration-time curve (AUC) was calculated from the 48 h serum concentration-time profile. In vivo metabolic activity was measured as the ratio AUCoxypurinol /AUCallopurinol. Results Although no strain-specific differences were observed in the AUCoxypurinol/AUCallopurinol ratio in the allopurinol (30 mg/kg)-treated group, the ratio in Jcl:SD rats was higher than that in Crl:CD rats after febuxostat pretreatment. Contrastingly, the AUC ratio of allopurinol (100 mg/kg) was approximately 2-fold higher in Jcl:SD rats than that in Crl:CD rats. These findings showed that Jcl:SD rats had higher intrinsic AO activity than Crl:CD rats did. However, febuxostat pretreatment substantially decreased the activity, as measured by the AUC ratio using allopurinol (100 mg/kg), to 46 and 63% in Crl:CD rats and Jcl:SD rats, respectively, compared to the control group without febuxostat pretreatment. Conclusions We elucidated the role of XO and AO in allopurinol metabolism in Crl:CD and Jcl:SD rats. Notably, AO can exert a proportionately greater impact on allopurinol metabolism at high allopurinol concentrations. AO's impact on allopurinol metabolism is meaningful enough that individual differences in AO may explain allopurinol toxicity events. Considering the inter-individual differences in AO activity, these findings can aid to dose adjustment of allopurinol to avoid potential adverse effects.